Scarcity and growth : the economics of natural resource availability - Barnett, Harold J. (Baltimore : Johns Hopkins Press, 1965)
The book is a reformulation of the theories of Malthus and his immediate associates and successors in the nineteenth-century stream of English classical economics by addressing the "man/land" or the "population/resources" problem afresh, in terms of the latest statistical information and modern analytical tools.
gp. 23/01/2019
loan